Proto-oncogene c-erbB2 initiates rat primordial follicle growth via PKC and MAPK pathways - Xiao-Yu Du; Ai-Xia Xu; Liang-Quan Xu; Jian Huang; Da-Lei Zhang; Li-Ping Zheng; Dan-Feng Tang; Yue-Hui Zheng (BMC, 2010)
Abstract Background c-erbB2, a proto-oncogene coding epidermal growth factor receptor-like receptor, also as a chemosensitivity/prognosis marker for gynecologic cancer, may be involved in initiation of growth of rat primordial follicles. The aim of the present study is to investigate the role and signal pathway of c-erbB2 in onset of rat primordial follicle development. Methods The expression of c-erbB2 mRNA and protein in neonatal ovaries cultured 4 and 8 days with/without epidermal growth factor (EGF) were examined by in situ hybridization, RT-PCR and western blot. The function of c-erbB2 in the primordial folliculogenesis was abolished by small interfering RNA transfection. Furthermore, MAPK inhibitor PD98059 and PKC inhibitor calphostin were used to explore the possible signaling pathway of c-erbB2 in primordial folliculogenesis. Results The results showed that c-erbB2 mRNA was expressed in ooplasm and the expression of c-erbB2 decreased after transfection with c-erbB2 siRNA. Treatment with EGF at 50 ng/ml significantly increased c-erbB2 expression and primary and secondary follicle formation in ovaries. However, this augmenting effect was remarkably inhibited by c-erbB2 siRNA transfection. Furthermore, folliculogenesis offset was blocked by calphostin (5 × 10(-4) mmol/L) and PD98059 (5 × 10(-2) mmol/L), but both did not down-regulate c-erbB2 expression. In contrast, the expressions of p-ERK and p-PKC were decreased obviously by c-erbB2 siRNA transfection. Conclusions c-erbB2 initiates rat primordial follicle growth via PKC and MAPK pathways, suggesting an important role of c-erbB2 in rat primordial follicle initiation and development.